Rival Consolidation in Nascent Insurrections: why Some Militant Groups Wage Sustained Insurgencies - Shkolnik, Michael (Perspectives on terrorism, 2021)
Why do some militant groups wage sustained insurgencies while other groups do not? This study shows that shifts in nascent rival relations between militant groups, from competition to consolidation, are key to understanding this puzzle. A militant group which has consolidated its rivals—whether by destruction, merger, or hegemonic dominance—should be in a stronger position to fight the target state than groups preoccupied with counterproductive violence against rivals within a militant movement. This study uses a multi-method, three-stage, research design starting with a novel quantitative regression analysis of 246 prominent militant groups worldwide from 1970-2007, featured in the Global Terrorism Database. I find that, on average, organizational capacity and constituency dominance are stronger indicators for engagement in sustained insurgencies than traditional proxies for observable group capabilities, thereby challenging conventional wisdom. The second stage focuses on a more bounded population (Middle Eastern and North African insurgent groups) and uses cross-case comparative methods to build my theory based on three forms of primary rival relations: competition (infighting or outbidding), strategic alliance, and hegemonic consolidation. Process-tracing methods are also used to explore within-case inferences and identify causal mechanisms in three diverse case studies: Hezbollah, the Kurdistan Workers’ Party (PKK), and the Syrian Muslim Brotherhood. Rival consolidation helps dominant groups mobilize resources effectively and overcome two major organizational hurdles: collective action and principal-agent problems. Without major competitors, dominant groups attract recruits and support, while militant leaders divert their attention to strengthening organizational capacity and preparing for war with the target state. My temporal theory of rival consolidation offers a more compelling explanation that accounts for the timing of insurgency onset, compared to scholarly arguments that rely on largely static factors or remain incomplete. From a policy perspective, this study challenges assumptions and presents a generalizable framework identifying nascent rival relations as a pragmatic indicator that can help counterterrorism analysts and practitioners better anticipate potential insurgent threats.